Tauhid Dan Spiritualitas Sebagai Dasar Pendidikan Islam Dalam Pandangan Hamka - Sayuti (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2020)
The tendency to secularize education seems to be very strong, for example from the system and learning taken by students who are processed that are intended for struggle and material, such as career, position, power, and money. It is as if their minds are the goal of education solely to complete worldly success. Producing output to be completely materialistic, consumeristic, and even not uncommon for hedonists. Because that's where the need to return to monotheism as a basic foundation which is the goal of Islamic education itself is a happy world and the hereafter. This study discusses the understanding of monotheism and the spirituality of education and understands the urgency of Islamic education in the view of Hamka as well as understanding the values ​​contained in monotheism and the spirituality of education. This research uses a descriptive-analytic research method that is using research library data collection techniques. Analysis of the data used in this research is content analysis (content analysis). The results of the study note that monotheism is not only talking in the area of ​​God but more than that monotheism as the basis and spirit of Islamic education. And in education can not escape from the values ​​of spirituality, namely the value of ubudiyah spirituality in education, the value of faith, and moral values. The thought contribution of this research consists of discussion in the field of Islamic education from books on monotheism and education and understanding the urgency of monotheism and the spirituality of education as the basis of Islamic education according to Hamka's point of view and providing explanations related to monotheism and the spirituality of education and values contained in it.